Transformasi Digital Manajemen Pelatihan Internal Staf dengan Pendekatan Extreme Programming - Tasya Nurul Fadilah; Santoso, Heni Rachmawati; Qudsi, Dini Hidayatul (Jurnal Komputer Terapan, 2025)
Internal training activities at the Information Technology Department of Politeknik Caltex Riau were previously managed in a semi-manual manner without an integrated database, leading to inefficiencies in administrative processes such as identifying potential trainers, participant registration, material documentation, and reporting. These issues resulted in disorganized data management and the risk of losing important information. This study aims to develop a web-based Training Management Information System using the Extreme Programming (XP) method as a solution to improve efficiency and service quality. The development process follows the XP stages: exploration (identifying user needs), planning (scheduling and estimating resources), development iterations (analysis, design, incremental releases, and feedback), and final production (system release and refinement). System evaluation was conducted through usability testing using questionnaires for organizers and lecturers, as well as in-depth interviews with the Head of Department as a strategic user. The results show that 79% of respondents found the system easy to use, relevant to their needs, and functionally adequate. Interviews also confirmed that the system met expectations in terms of features and interface design. These findings indicate that the XP approach is effective in developing user-centered web-based systems and improving the operational efficiency of internal training activities.